Thematic E-Modules Using the PjBL Model Based on STEAM to Enhance Science Literacy and HOTS - Dalifa, Dalifa; Winarni, Endang Widi; Nirwana, Nirwana (IJIS Edu : Indonesian Journal of Integrated Science Education, 2024)
This research aims to develop a thematic E-module utilizing the Project-based Learning (PjBL) model based on STEAM (Science, Technology, Engineering, Arts, Mathematics) and to assess its effectiveness in improving science literacy and higher-order thinking skills among fourth-grade elementary school students. The development method utilized the Borg & Gall model. Research instruments included document analysis sheets, needs analysis sheets, and validation sheets. Data collection techniques involved document analysis, observation, questionnaires, and tests. Data obtained from product assessment sheets, test results, and questionnaires were analyzed both qualitatively and quantitatively. The results indicate that the developed E-Module has demonstrated high levels of validity and effectiveness in enhancing science literacy and higher-order thinking skills among fourth-grade elementary students. Material validity was evaluated using Aiken’s V, with an average score of 0.90 (very valid), and a validator agreement rate of 0.92% (almost perfect). Language and design validity were also found to be high, with Aiken’s V scores of 0.91 (very valid) and 0.88 (very valid) respectively, and validator agreement rates of 0.80% (almost perfect) and 0.73% (strong) respectively. Based on the calculation of gain scores, the experimental group achieved 0.47 (moderate) compared to the control group's score of 0.25 (low). Additionally, an independent sample t-test showed a significance value of 0.000 (sig <0.05) between the control and experimental groups, confirming the effectiveness of using this E-Module. This research provides a significant contribution to the development of innovative and effective learning materials aimed at enhancing science literacy and higher-order thinking skills among fourth-grade elementary students.